In search for employability strategy: Emergent approaches by higher education institutions - Sgobbi, F. (Higher Education, 2025)
This paper explores the formation of employability strategies in higher education institutions (HEIs), focusing on whether they result from deliberate planning or emerge organically from institutional dynamics. While employability is a key indicator of education quality, its integration into HEI strategic goals, plans, and practices remains underexplored, especially outside Anglo-Saxon contexts. Through case studies of four Italian and Portuguese HEIs, the study tests whether employability strategies are explicitly designed or evolve through a mix of top-down and bottom-up initiatives. The findings support the latter, showing that strategies often emerge through the ex post rationalisation of spontaneous actions and procedures. However, challenges like vaguely defined targets, poor communication, and resource limitations can fragment efforts and undermine sustainability. By shifting the focus from strategy classification to strategy formation, this study provides insights for HEIs still developing their own employability approaches.